Palm oil mill effluent (POME) precipitation using ammonium-intercalated clay coagulant - Priatna, Satria Jaya; Hakim, Yusuf Mathiinul; Alfarizi, Muhammad Afif; Sailah, Siti; Mohadi, Risfidian (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Clay intercalation has been completed to improve coagulation ability using ammonium ions intercalant via multi-step intercalation. The intercalated clay was confirmed by Scanning Electron Microscope-Energy Dispersive Spectroscopy analysis of expanded lamellar and reduction impurities. Fourier Transform Infra-Red analysis confirmed the sharp and strong peak adsorption at 1448 cm-1 as ammonium (NH4+) bendingvibration, and X-Ray Diffraction analysis confirmed the peak shifting to smaller 2? at 10.08° as increasing basal spacing because of ammonium ion intercalated. The Palm Oil Mill Effluent (POME) coagulation was carried out using contact time and coagulant dose variations to determine the optimum conditions, reaching 45 minutes of coagulation and 0.4 g coagulant was used. Furthermore, the turbidity, free fatty acid, and total suspended solids were measured to reach the reduction values of 93%, 49.7%, and 73.7%, respectively. The reusable study of ammoniumintercalated clay confirmed the stability of the three cycles of coagulation used.